Pendidikan yang Memerdekakan, Memanusiakan dan Berpihak pada Murid - Silvia Wardani; Masduki Asbari; Kholid Ibnu Misri (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of this study is to find out about the new innovation from the Minister of Education and Culture, namely the Driving Teacher Program, which is expected to be able to produce as many agents of transformation as possible in the educational ecosystem who are able to produce students with global competence and Pancasila character. This study report uses a descriptive qualitative method by taking note-taking because the data source was obtained by listening to oral narratives from the Indonesian Ministry of Education and Culture's YouTube channel entitled